Prevalence of Malnutritionand Associated Factors among Children Aged 6–24 Months under Poverty Alleviation Policy In Shanxi Province, China: A Cross-sectional Study. - Minli Zhang; Nelbon Giloi; Yang Shen; Yan Yu; M.Y.Aza Sherin; Mei Ching Lim (Elsevier, 2024)
Indexed by WOS/ Scopus